THE IMPACT OF INPATIENT DIET ORDERS ON PATIENT NUTRITION AND DIETARY BEHAVIORS POST DISCHARGE - Lily Nedda Dastmalchi; Ishaan Dharia; Leigh A. Frame (Elsevier, 2023)
Therapeutic Area: Nutrition, Lifestyle Background: Suboptimal nutrition is a known contributor to the development of cardiovascular disease. In the past decade, focus has been on improving the quality of hospital food with nutrition and policy science initiating programs, e.g. Healthy Food in Health Care. Little has been studied on the impact of these improvements on diet choices after discharge. To our knowledge, this is the first study to evaluate if inpatient diet orders play a role in nutrition after discharge. Methods: Patients ≥18 years of age admitted to the medicine service with either a regular or cardiac diet order were recruited. Exclusion criteria were the following dietary parameters-fluid restriction, low potassium, diabetic, gluten free, or vegan diets. Patients were given a baseline questionnaire using a Lickert scale to assess dietary behaviors, nutrition counseling during admission, and demographics. One month post-discharge, a follow-up questionnaire was given to reassess their dietary choices. Results: In this preliminary analysis, 70 subjects were enrolled: 57.1% (n= 40) regular diet and 42.0% (n=30) cardiac diet. 38.6% (n=27) believed diet orders during admission were part of the their medical treatment. At follow-up, 55 patients remained and included in the final analysis. 50 with identifiable subject IDs: 57.4% (n= 27) regular diet and 42.5% (n=20) cardiac diet. 15 were lost to follow up: 1 deceased, 2 declined to participate, 2 were readmitted to the hospital, and the remaining were not reachable. Diet was reported as always important to overall health 50.0% (n=35) at baseline vs 72.7% (n=40, p= 0.642) at follow up. 22.8% (n=16) of subjects stated never reading nutrition labels in comparison to follow-up 12.7% (n=7, p= 0.019). Never monitoring salt intake was reported among 23.6% (n=9) patients at baseline and 12.7% at follow-up (n=6, p=0.043). Subjects reported that nutrition education was never received during their inpatient or outpatient follow up period (30% (n=21) vs 76.3% (n=42), p=0.0002). Conclusions: To-date, our pilot study shows inpatient diet orders having the potential to influence dietary behaviors with significant changes in food label reading and monitoring salt intake after discharge. Nutrition education was significantly never given in both inpatient and outpatient settings. However, most patients believe nutrition is important to their overall health, further supporting receptivity to nutrition education during inpatient and outpatient follow-up education.